Polityka administracyjna a samorządowa polityka oświatowa — na gruncie nauk prawnoadministracyjnych - Raszewska-Skałecka, Renata (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Present-day factors of public administration, variability of educational law, uncertainty of state educational policy in the scope of educational reform, its political instrumentalization. These are exemplary factors of changes which have impact on educational policy of local self-government and ways of realization public tasks.Local education as the sphere of public administration activity has changed rapidly in recent years and often shows differences between expectations and fulfillment of social needs in the scope of education.
Keywords: public administration; state educational policy; educational law